FEATURES OF THE EDUCATIONAL PROGRAM IN FOREIGN UNIVERSITIES: ON THE EXAMPLE OF THE MEDICAL COLLEGE OF UNIVERSITY OF CENTRAL FLORIDA, USA - Shadmanov, A.K.; Kawell, Z.; Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The University of Central Florida (UCF) is a metropolitan research university built to make a better future for our students and society. We solve tomorrow’s greatest challenges through a commitment to academic, inclusive and operational excellence. Leveraging innovative learning, discovery and partnerships, we foster social mobility while developing the skilled talent needed to advance industry for our region, state and beyond.